Stres di tempat kerja: isu global dalam melestarikan organisasi - Zafir Mohd Makhbul; Nor Liza Abdullah; Noor Azuan Hashim (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
Work stress problems should not be taken lightly by the organization and it is a global issue that gives huge impact on organizational productivity. Stress is also a major issue in terms of occupational safety and health. Literature review clearly shows that stress at the workplace is commonly associated with cost and organizational productivity. Actually, stress at the workplace is not a new phenomenon in working environment. It exists in every organization and no one could evade from stress. Stress at the workplace issues get major interest in Japan and United States organizations since the problem is strongly related to overall organizational performance. In England and Wales, stress at the workplace is among top three categories of the largest disease caused by working environment. World Health Organization (WHO) believes that stress at the workplace problem will become a major threat to human health by year 2020. Stress is not an occupational problem that should be taken lightly. Although every employee worldwide will experience this problem, but the question is how they can survive when stress become uncontrolled. This issue should be given serious attention by every organization in the world. Furthermore, technological change, social and discontinuation in the employment sector will make this problem a serious global issue.